Effects of Sucrose Palmitate on the Physico-Chemical and Mucoadhesive Properties of Buccal Films - András Kelemen; Bálint Katona; Szilvia Módra; Zoltán Aigner; István Sebe; Klára Pintye-Hódi; Romána Zelkó; Géza Regdon; Katalin Kristó (Molecules, 2020)
In our current research, sucrose palmitate (SP) was applied as a possible permeation enhancer for buccal use. This route of administration is a novelty as there is no literature on the use of SP in buccal mucoadhesive films. Films containing SP were prepared at different temperatures, with different concentrations of SP and different lengths of hydroxypropyl methylcellulose (HPMC) chains. The mechanical, structural, and in vitro mucoadhesive properties of films containing SP were investigated. Tensile strength and mucoadhesive force were measured with a device and software developed in our Institute. Positron annihilation lifetime spectroscopy (PALS) and X-ray powder diffractometry (XRPD) were applied for the structure analysis of the films. Mucoadhesive work was calculated in two ways: from the measured contact angle and compared with direct mucoadhesive work, which measured mucoadhesive force, which is direct mucoadhesion work. These results correlate linearly with a correlation coefficient of 0.98. It is also novel because it is a new method for the determination of mucoadhesive work.